(untitled) (Bangladesh Journal of Botany, 2024)
Salinity has detrimental effects on rice’s morphological, physiological, and biochemical traits, which significantly impedes development and yield. This study examined differences in total antioxidant capacity (DPPH), total phenolic (TPC), and flavonoid (TFC) content in four different Oryza sativa L. types (Karacadağ, Gala, Tunca, and Aromatik-1) that were exposed to different salt concentrations (0, 100, 200, and 300 mM NaCl). The highest increase in both TPC and TFC was observed in 300 mM NaCl application of Tunca (91 and 83%, respectively). Out of all the applications, the highest decrease in TPC and TFC was at 100 mM NaCl of Aromatik-1 (68 and 60%, respectively) as compared to the control. In terms of the total antioxidant capacity, NaCl applications of Gala, Tunca and Aromatik-1 at 400-1000 µg/ml concentrations were higher than BHT used as positive control. Within the rice varieties, the concentrations of Tunca at 100, 200, and 300 mM NaCl demonstrated high rates of free radical scavenging activity (80.08, 80.18, and 79.67, respectively). Bangladesh J. Bot. 53(1): 67-74, 2024 (March)